Integrating Technology, Management and Marketing Innovation through Open Innovation Models - Vega-Jurado,Jaider (Universidad Alberto Hurtado. Facultad de Economía y Negocios, 2015)
This paper explores, through a company case study, the importance of innovation for the competitive development of a company and how the adoption of an open innovation strategy could be effective to face typical barriers associated with the implementation of such processes. The case analysis shows the importance of the University-Industry relationship and the relevant role that the government plays in fomenting these relationships. Likewise, we point out the value of adopting an integral vision of the innovation process that not only considers its technological dimension (new product development), but also the elements associated to marketing and organizational change practices. The case studied herein exemplifies the systemic character of innovation and the relevance it has for companies, particularly for SME's, to open its innovation strategy and integrate themselves with other actors to leverage its cognitive and financial resources as well as to explore new routes to bring the best of its internal technological capacities.